Functionalization of cardanol: towards biobased polymers and additives - Voirin, Coline; Caillol, Sylvain; Sadavarte, Nilakshi V.; Tawade, Bhausaheb V.; Boutevin, Bernard; Wadgaonkar, Prakash P. (Polymer Chemistry, 2014)
Among the renewable resource materials, cashew nut shell liquid (CNSL) is considered as an important starting material due to its unique structural features, abundant availability and low cost. A large number of chemicals and products have been developed starting from CNSL by taking advantage of the three reactive sites, namely, phenolic hydroxyl, aromatic ring and unsaturation(s) in the alkenyl side chain. This comprehensive review deals with general information on CNSL, its purification and separation methods, reactivity and applications in polymer chemistry.